Answer:
-2, -4, -3 + 2i, -3-2i
Step-by-step explanation:
Equaling the function to zero we have:
(x ^ 2 + 6x + 8) (x ^ 2 + 6x + 13) = 0
For the first parenthesis we have:
(x ^ 2 + 6x + 8) = 0\\(x + 4) (x + 2) = 0
Therefore the roots are:
x = - 4\\x = - 2
For the second parenthesis we have:
(x ^ 2 + 6x + 13) = 0
By completing squares we have:
x ^ 2 + 6x = -13
x ^ 2 + 6x + (\frac{6}{2}) ^ 2 = -13 + (\frac{6}{2}) ^ 2\\x ^ 2 + 6x + 9 = -13 + 9\\(x + 3) ^ 2 = - 4\\x + 3 = +/- \sqrt{-4}
Therefore the roots are:
x = -3 + 2i\\x = -3 - 2i
Hope this was helpful
Step-by-step explanation:
From Pythagorean theorem, one of the sides can be determined as x^2 + y^2 =8^2
or y = (8^2 - x^2)^(1/2)
we can write the perimeter P as
P = 2x + 2y ---> 20 = 2x + 2(8^2 - x^2)^(1/2)
Dividing by 2, we get
10 = x + (8^2 - x^2)^(1/2)
Move the x to the other side,
10 - x = (8^2 - x^2)^(1/2)
Take the square of both sides to get rid of the radical sign:
(10 - x)^2 = 8^2 - x^2
Move everything to the left and expand the quantity inside the parenthesis:
x^2 + (100 - 20x + x^2) - 64 = 0
2x^2 - 20x + 64 = 0
or
x^2 - 10x + 32 = 0
Now we can see that a = -10 and b = 32
<span>18.345 - 10.67 = 7.675</span>
Pretty sure it’s 16TXI, hope this helps!
Answer:
<h3>
-2a³ + 9a² + 6ab² + 45a + 18b² </h3>
Step-by-step explanation:
(a + 3)×(−2a² + 15a + 6b²) =
= a×(−2a² + 15a + 6b²) + 3×(−2a² + 15a + 6b²) =
= -2a³ + <u>15a²</u> + 6ab² - <u>6a²</u> + 45a + 18b² =
= -2a³ + 9a² + 6ab² + 45a + 18b²